Synthesis of polysarcosine from air and moisture stable N-phenoxycarbonyl-N-methylglycine assisted by tertiary amine base. Issue 18 (14th April 2016) - Doriti, Afroditi; Brosnan, Sarah M.; Weidner, Steffen M.; Schlaad, Helmut
Abstract : Well-defined polysarcosines are synthesized from a stable urethane derivative of N -methylglycine, avoiding the direct use of NCA. Abstract : Polysarcosine ( M n = 3650–20 000 g mol −1, Đ ∼ 1.1) was synthesized from the air and moisture stable N -phenoxycarbonyl- N -methylglycine. Polymerization was achieved by in situ transformation of the urethane precursor into the corresponding N -methylglycine- N -carboxyanhydride, when in the presence of a non-nucleophilic tertiary amine base and a primary amine initiator.